Resilience of MSMEs in Indonesia Post-Pandemic: Bibliometric Analysis of Digital Transformation - Hidayat, Husnil; Susanto, Perengki; patrisia, dina (JURNAL MANAJEMEN MOTIVASI, 2026)
This study explores the resilience of Indonesian MSMEs in the post-pandemic era through a bibliometric analysis of digital transformation literature. Using data from Scopus (2022–2025) and the Biblioshiny application, 91 articles were analyzed. Results show growing academic interest in digital resilience, business model innovation, and strategic adaptation. Key themes include digital commerce, social media, and technological innovation. The findings offer implications for theory and policy on SME transformation in developing economies, especially Indonesia. This study provides a comprehensive mapping of conceptual structures and future research directions in the digital adaptation of MSMEs.